The Implementation of Performance-Based Budgeting Through A Money Follow Program in Impressing Budget Corruption - Dadang Suwanda; Reydonnyzar Moenek; Sampara Lukman; Muhammad Syaifullah (Universitas Batanghari Jambi, 2021)
Performance-based budgeting is an integrated annual performance planning which shows the relationship between the funding level and the program desired outcome while money follow program concept is a budgeting approach focusing on programs/activities related to local priorities which have a direct impact on the society. This study aims to evaluate the implementation of performance-based budgeting with money follow program concept in local government planning and budgeting. This study used a qualitative descriptive analysis approach from budget data taken off during 2017-2019. The indicators used in evaluating performance-based budgeting were the establishment of organizational strategies, activities determination and performance evaluation of previous periods. The results showed that the local government had implemented a performance-based budgeting with money follow program concept in their planning and budgeting activities. This could be seen from their establishment of organizational strategies (visions, missions, goals and objectives), activities determinations, and previous period performance evaluations.